MENINGKATKAN PEMBELIAN ULANG MELALUI KEPERCAYAAN DAN KEPUASAN PADA PEMBELANJAAN ONLINE - Siyamtinah -; Hendar - (Conference In Business, Accounting, And Management (CBAM), 2015)
This study aims to examine the effect of quality of service, satisfaction, utilitarian value, confidence in the re-purchase on online purchases. The research problem is how to increase trust and repeat purchase at online shopping. The sample in this research is the students of economic faculties Unissula Semarang as many as 198 people consisting of students one semester to semester five, using purposive sampling method, technique of data collection conducted by survey through interviews and questionnaires. Data analysis was performed by descriptive analysis method and the method of Partial Least Square (PLS). The result showed that the economic faculty students on average make purchases online through social media such as BBM and Facebook. The results of data analysis using the PLS indicates that there is a positive and significant influence between utilitarian value, satisfaction, confidence in the repeat purchase. But the variable quality of services to satisfaction as well as satisfaction with the confidence showed no significant results. Based on the research results, repeat purchase can be enhanced through the value of benefits and confidence in the use of social media. Keywords: service quality, satisfaction, the value of benefits, trust and repeat purchase